TJ-M2010-5, a novel CNS drug candidate, attenuates acute cerebral ischemia-reperfusion injury through the MyD88/NF-κB and ERK pathway - Li, Zeyang; Zhao, Minghui; Zhang, Xiaoqian; Lu, Yiran; Yang, Yang; Xie, Yalong; Zou, Zhimiao; Zhou, Liang; Shang, Runshi; Zhang, Limin; Jiang, Fengchao; Du, Dunfeng; et al. (Frontiers in Pharmacology, 2022)
Background: Cerebral ischemia-reperfusion injury (CIRI) inevitably occurs after vascular recanalization treatment for ischemic stroke. The accompanying inflammatory cascades have a major impact on outcome and regeneration after ischemic stroke. Evidences have demonstrated that TLR/MyD88/NF-κB signaling contributes to CIRI. This study aimed to investigate the druggability of MyD88 in the central nervous system (CNS) and the neuroprotective and anti-neuroinflammatory effects of the MyD88 inhibitor TJ-M2010-5 on CIRI. Methods: A middle cerebral artery occlusion (MCAO) model was used to simulate CIRI in mice. BV-2 cells were stimulated with oxygen glucose deprivation/reoxygenation (OGD/R) or lipopolysaccharide, and SH-SY5Y cells were induced by OGD/R in vitro. Neurological deficit scores and cerebral infarction volumes were evaluated. Immunofluorescence staining was performed to measure neuronal damage and apoptosis in the brain. The anti-neuroinflammatory effect of TJ-M2010-5 was evaluated by analyzing the expression of inflammatory cytokines, activation of microglia, and infiltration of peripheral myeloid cells. The expression of proteins of the MyD88/NF-κB and ERK pathway was detected by Simple Western. The concentrations of TJ-M2010-5 in the blood and brain were analyzed by liquid chromatography-mass spectrometry. Results: The cerebral infarction volume decreased in mice treated with TJ-M2010-5, with the most prominent decrease being approximately 80% of the original infarction volume. Neuronal loss and apoptosis were reduced following TJ-M2010-5 treatment. TJ-M2010-5 inhibited the infiltration of peripheral myeloid cells and the activation of microglia. TJ-M2010-5 also downregulated the expression of inflammatory cytokines and inhibited the MyD88/NF-κB and ERK pathway. Furthermore, TJ-M2010-5 showed good blood-brain barrier permeability and no neurotoxicity. Conclusion: TJ-M2010-5 has an excellent therapeutic effect on CIRI as a novel CNS drug candidate by inhibiting excessive neuroinflammatory responses.